Engineering approaches for improving the removal of organic micropollutants in anaerobic reactors: microaeration, redox mediator, and nitrate addition - Nascimento, José Gilmar da Silva do (2020)
In recent decades, organic micropollutants (MPOs), such as pharmaceuticals, pesticides, hormones, personal care products and others, have attracted a lot of attention due to their possible negative impacts on ecosystems and public health. In general, wastewater treatment plants (WWTPs) are not specifically designed to remove MPOs, and although removal efficiencies (ERs) depend on the compound and treatment technology, they are generally limited, especially in anaerobic systems operated with short turnaround times. hydraulic retention (TDHs <10h). Therefore, this work evaluated, through four studies, some engineering approaches, such as the addition of microaeration, redox mediator and nitrate, to increase the ASERs of different MPOs (hormones, pharmaceuticals, bisphenol A and parabens) in anaerobic sludge blanket reactors and upflow (anerobic sludge blanket, UASB) operated with a 7-8 HDD during the treatment of synthetic sewage containing 200 μg · L-1 of each compound.In the first study, the effect of increased microaeration flow rates (1-6 mL of air ∙ min-1) in the biotransformation of seven MPOs (estrone, 17β-estradiol, 17α-ethinylestradiol, bisphenol A, diclofenac, sulfamethoxazole and trimethoprim) was evaluated. Microaeration improved REs significantly, and the best results were obtained with 4 mL of air · min-1 (~ 90%). In the second study, the effect of the redox mediator anthraquinone-2,6-disulfonate (AQDS) (50 and 100 μM), associated or not with microaeration (1 mL of air ∙ min-1), and of different oxygen demand-chemical relationships (COD) ) / NO3- (2.5-10) in the ERs of the antibiotics sulfamethoxazole and trimethoprim was investigated. The AQDS significantly accelerated the anaerobic biotransformation of antibiotics (a ~ 70% (<17%), but had a more significant effect on compounds with longer alkyl chains (ethylparaben, propylparaben and butylparaben) (ERs> 90% with 100 μM AQDS) than on methylparaben (~ 54% ER with 50 or 100 μM AQDS). Under microaerobic conditions, AQDS had a limited impact on the biotransformation of longer alkyl chain parabens and even compromised the effect of oxygen on MeP biotransformation, that is, AQDS had an antagonistic effect on microaeration. Finally, in all studies, the reactors remained remarkably stable, with a high average COD ER (85-90%), without accumulation of volatile fatty acids and pH values ​​close to the neutral rangeincrease in REs with 100 μM of AQDS). Microaeration improved its biotransformation, even in the presence of AQDS, when the best ERs were obtained (> 70%), particularly for trimethoprim (~ 90% with 1 mL of air · min-1 and 100 μM of AQDS). The addition of nitrate also showed promising results, with the highest REs (~ 85%) being achieved in the lowest COD / NO3- ratio (2.5). In the third study, the effect of different microaeration flow rates (1-4 mL of air · min-1) on the ERs of four parabens (methylparaben, ethylparaben, propylparaben) was evaluated and butylparaben). Low ERs (14-20%) were achieved under anaerobic conditions, but the addition of just 1 mL of air · min-1 significantly boosted the biotransformation of parabens, ensuring ERs above 85% for all compounds. In the fourth study, the individual and combined effects of the AQDS redox mediator (50 and 100 μM) and micro-aeration (1 mL of air · min-1) on the biotransformation of the same parabens were evaluated. AQDS has considerably improved the low ERs of all parabens